Por uma cínica do impesoal: articulaçoes entre o corpo e o tempo - Debenetti, Carmen Ines; Galli Fonseca, Tania Maria (Revista Subjetividades, 2006)
Por uma cínica do impesoal: articulaçoes entre o corpo e o tempo